The Influence of Facilities, Competence and Work Motivation on the Performance of Sei Rumbiya Plantation Employees at PT Pp. London Sumatra Indonesia Tbk - Darma, Surya Darma; Ingan Malem Tarigan; Mangasi Sinurat; Chrisin Natalia Sianipar (Amkop Management Accounting Review (AMAR), 2025)
This study seeks to explore the extent to which workplace facilities, employee competence, and motivation influence employee performance at Sei Rumbiya Plantation, PT PP. London Sumatra Indonesia Tbk. Using a quantitative approach, data were analyzed through multiple linear regression. The findings reveal that, partially, both facility and competence variables do not significantly affect employee performance, as indicated by t-values (0.021 and -2.497, respectively) being lower than the critical value. In contrast, motivation demonstrated a significant positive impact, with a t-value of 3.002. Simultaneously, all three variables collectively exert a significant influence on performance, although their overall contribution remains modest at 13.2%. The remaining 86.8% is attributed to other factors beyond the scope of this study. These results underscore the central role of intrinsic motivation in shaping productive, human-centered work environments and emphasize the need to look beyond physical and technical enablers when managing human resources in labor-intensive sectors.